Ethical Leadership and Organizational Commitment: Mediating Role of Psychological Empowerment - Basnet, Bhupindra Jung; Neupane, Rabindra Kumar (NPRC Journal of Multidisciplinary Research, 2025)
This study aim was to analyze the influence of EL on OC intervened by psychological empowerment. The research design has used descriptive and casual-comparative research design. 348 respondents from permanent employees in Nepali public service sector as sample size. Data was collected through the structural questionnaire. Structural equation modeling has been applied to examine the direct and indirect effect. The results exposed that EL positively and significantly influenced OC. Psychological empowerment partially intervened in the affiliation between EL and OC. Psychological empowerment is important component in Nepali public service sector that enhance the connection between EL and OC.